Integrating knowledge systems in South African school education as crises response : re-focusing on epistemological questions - Seehawer, Maren (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
Situated in ongoing scholarly reflections on how to respond to interconnected educational, epistemological and colonial crises, the article proposes that a bold giant leap scenario for transforming South Africa’s school education system may be one such response. To that end, the article engages with discourses on integrating indigenous and Euro-Western knowledge systems. The article argues for a holistic rather than tokenistic integration – one that requires examining epistemological assumptions and revisiting basic questions such as why, what, and how to integrate indigenous knowing. It suggests (re-) installing Ubuntu as an overarching rationale for integrating knowledge systems. Drawing on this rationale and on insights from a participatory action research study, the article makes several recommendations to inform future research and policy work: recognising the global importance of local indigenous practices; position teachers as facilitators of dialogue between epistemologies; combine approaches of teaching both non-predefined and predefined indigenous knowing; develop epistemologically appropriate ways to represent indigenous knowing in curricula and textbooks
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 5, Volume 9, 2025 Special Issue
Keywords: Education system; Indigenous knowing; Integrating knowledge systems; South Africa; Sustainability; Ubuntu; Ubuntu (Philosophy); Education -- South Africa; Ethnoscience -- South Africa; Knowledge, Theory of